Makna Doangang Kasalamakkang Dalam Masyarakat Makassar - Annisa Asywa Fahrani; Johar Amir; Hajrah Hajrah (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. The purpose of this study is to describe the meaning of denotation and the meaning of connotation in doangang kasalamakang in Makassar society using Roland Barthes' theory of Semiotics in the theory of denotation meaning and connotation meaning. The data in this study used interview, record, document, and record research techniques. The results of this study show that (1) The meaning of the denotation obtained from doangang kasalamakkang as a whole has a meaning about a situation, when a person wants to realize his desires, prosper his life, and can strengthen his stance. Through this desire, it can be blessed and protected by Allah SWT. Then, the meaning of connotation (2) obtained refers to a person's request, namely the user of doangang kasalamakkang as a person who wants his request to come true. Doangang kasalamakkang users also describe that he has always prayed in his daily life, so users hope that his wishes will come true. Hoping that he will always be under the protection of Allah Almighty. Doangang Kasalamakkang users also want to tell readers that Doangang is a guide on how to live and protect themselves, and how to establish relationships between humans and creators.Keywords: Meaning, Doangang Kasalamakkang, Roland Barthes Semiotics